2012
DOI: 10.1016/j.bbamcr.2012.02.014
|View full text |Cite
|
Sign up to set email alerts
|

MiR-217 is involved in Tat-induced HIV-1 long terminal repeat (LTR) transactivation by down-regulation of SIRT1

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression and may contribute to the development and progression of many infective diseases including human immunodeficiency virus 1 (HIV-1) infection. The Tat protein is fundamental to viral gene expression. In this study, our goal was to investigate the regulation of a specific miRNA (known as miR-217) in multinuclear activation of galactosidase indicator (MAGI) cells and explore the mechanisms by which miR-217 influenced Tat-induced HIV-1 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 43 publications
1
48
1
Order By: Relevance
“…In cultured mouse AML-12 hepatocytes and in mouse livers, miR-217 promotes ethanol-induced fat accumulation by down-regulating SirT1 [16]. miR-217 also influences Tatinduced HIV-1 long terminal repeat (LTR) transactivation by down-regulation of SirT1 expression [17].It has been reported that miR-217 acts as a potential tumor suppressor in pancreatic ductal adenocarcinoma by targeting KRAS [8]. Overexpression of miR-217 can reverse the malignant behavior of pancreatic ductal adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured mouse AML-12 hepatocytes and in mouse livers, miR-217 promotes ethanol-induced fat accumulation by down-regulating SirT1 [16]. miR-217 also influences Tatinduced HIV-1 long terminal repeat (LTR) transactivation by down-regulation of SirT1 expression [17].It has been reported that miR-217 acts as a potential tumor suppressor in pancreatic ductal adenocarcinoma by targeting KRAS [8]. Overexpression of miR-217 can reverse the malignant behavior of pancreatic ductal adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Independently, miR-17-5p and miR20a were found by a separate group to target p300/CBPassociated factor (PCAF), another cellular cofactor of the viral Tat protein (29), and a further set of six miRNAs (miR15a, miR-15b, miR-16, miR-20a, miR-93, and miR-106b) were reported to repress the expression of a third Tat cofactor, Pur-␣, which was noted also to be enriched in monocytes (45). In a converse example, Zhang et al (46) found that miR-217 was induced by Tat and that miR-217 increased HIV-1 expression by targeting SIRT-1 (sirtuin-1), a host protein that deacetylates and inactivates Tat function. Collectively, these discrete findings illustrate the complex miRNA-FIGURE 1.…”
Section: Cellular Mirnas Regulate Hiv-1 Expressionmentioning
confidence: 99%
“…In the same years, Zhang et al found that miR-217 was induced by tat and that miR-217 increased HIV-1 expression by targeting SIRT-a (sirtuin-1), a host protein that deacetylates and inactivates tat function [53]. These findings, all together, illustrate the complex miRNAmediated positive and negative regulatory events that influence viral replication.…”
Section: Silencing Of Cellular Mrnas Sequences That Encode Host Cell mentioning
confidence: 73%